2007
DOI: 10.1371/journal.pmed.0040129
|View full text |Cite
|
Sign up to set email alerts
|

HIV Treatment in a Conflict Setting: Outcomes and Experiences from Bukavu, Democratic Republic of the Congo

Abstract: Providing HIV care in conflict settings involves additional obstacles to those generally encountered in other resource-limited settings, say Heather Culbert and colleagues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 12 publications
5
77
0
1
Order By: Relevance
“…40 Finally, operational research that is published in a peer-reviewed journal can aff ect policy change outside the confi nes of a particular programme. For example, the study by Culbert and colleagues, 42 which provided knowledge on the feasibility of off ering antiretroviral therapy during confl ict in the Democratic Republic of the Congo, led to a change in the Sphere Project's humanitarian charter and the adoption of minimum standards in humanitarian responses (previously this benchmark reference for NGOs advised against off ering antiretroviral therapy in such settings). 43 Despite the importance of publication as a way to share knowledge, a substantial proportion of operational research studies in low-income and middle-income countries are never published in scientifi c journals.…”
Section: Dissemination Of Research Resultsmentioning
confidence: 99%
“…40 Finally, operational research that is published in a peer-reviewed journal can aff ect policy change outside the confi nes of a particular programme. For example, the study by Culbert and colleagues, 42 which provided knowledge on the feasibility of off ering antiretroviral therapy during confl ict in the Democratic Republic of the Congo, led to a change in the Sphere Project's humanitarian charter and the adoption of minimum standards in humanitarian responses (previously this benchmark reference for NGOs advised against off ering antiretroviral therapy in such settings). 43 Despite the importance of publication as a way to share knowledge, a substantial proportion of operational research studies in low-income and middle-income countries are never published in scientifi c journals.…”
Section: Dissemination Of Research Resultsmentioning
confidence: 99%
“…Research in these areas is, nevertheless, needed to better understand how to manage questions such as mental health issues in war zones, 36 treatment and diagnosis of neglected diseases, 37 or off ering of HIV/AIDS care in slum settings. For example, when the Sphere Project guidelines recommended against HIV therapy in confl ict settings, 38 an MSF study by Culbert and colleagues 16 proceeded anyway and showed good outcomes. The importance of contributing to sustainable and evidencebased change is being recognised within MSF, as shown by its rapidly growing scientifi c output.…”
Section: Personal Viewmentioning
confidence: 99%
“…15,17,19 To our knowledge, there has been no such finding in conflict situations in Africa, where most excess adult mortality is related to violence or acute infections rather than to chronic illnesses. 15,[19][20][21][22] Rates of HIV infection among IDPs and refugees in Africa can be high, although not necessarily higher than in the communities of origin [24][25][26][27][28] . In our analysis, the majority of adult IDP deaths were ascribed to HIV infection, which accounted for a larger proportion of deaths among IDPs than among DSS residents.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other studies have shown that HIV+ persons can be treated successfully in conflict settings, although the challenges of maintaining and initiating HIV care in rural, non-camp settings like western Kenya are greater than in urban settings or IDP camps where the population is more confined and accessible. 24,25,27,30,31 …”
Section: Discussionmentioning
confidence: 99%